SIGNIFICANCE OF APOPTOSIS AND CELL PROLIFERATION MARKERS IN THYROID PAPILLARY MICROCARCINOMA - Muzhichuk, A. V.; Afanaseva, N. I.; Muzhichuk, V. V.; Starikov, V. I.; Vinnik, Y. A.; Mihalitsyn, V. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
76 samples of removed thyroid gland tissue were studied. In 11 of them thyroid microcarcinoma was diagnosed. We analyzed the results of immunohistochemical staining for p53, p21WAF1/CIP1 and p63. We compared the expression of these markers in microcarcinoma and paratumor tissues in comparison with tumors of larger size. Established that expression level of the main control gene (p53), proliferative activity index (Ki-67), in papillary microcarcinoma not differ for the better from larger size tumors. Proliferation and apoptosis markers expression in benign paratumor microcarcinoma tissue, had similarities with indicators of markers expression as in microcarcinomas tumor or in "large" cancer. This may indicate the occurrence of a malignant tumor growth from benign tumors.